2011
DOI: 10.1017/s1368980010003435
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of adherence to nutritional therapy in malnourished adult AIDS patients in Kenya

Abstract: Objective: To understand factors affecting the compliance of malnourished,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 12 publications
15
76
0
2
Order By: Relevance
“…Among the identified confounders, it can be speculated that throat sores reduce the swallowing capacity of the patients. A qualitative study on the compliance of the use of P-RUTF achieved a similar conclusion [23]. In SAM patients, cases of swallowing difficulty need to be detected early by medical staff and ideally addressed with appropriate in-patient care using therapeutic milk formulas (F75 and F100) [31].…”
Section: The Acceptability Of Sms-rutfhmentioning
confidence: 82%
See 1 more Smart Citation
“…Among the identified confounders, it can be speculated that throat sores reduce the swallowing capacity of the patients. A qualitative study on the compliance of the use of P-RUTF achieved a similar conclusion [23]. In SAM patients, cases of swallowing difficulty need to be detected early by medical staff and ideally addressed with appropriate in-patient care using therapeutic milk formulas (F75 and F100) [31].…”
Section: The Acceptability Of Sms-rutfhmentioning
confidence: 82%
“…The most common commercial brand of RUTF is Plumpy'nut [17], which was designed for pediatric use and is the only one that has been clinically tested in several different studies [3,[18][19][20][21][22]. In wasted adults, a number of factors have been shown to reduce compliance with Plumpy'nut including the taste of this pediatric formulation [23]. Moreover, the micronutrient densities in Plumpy'nut might not be appropriate for the needs of wasted adults with HIV/TB.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that the potential nutritional supplements were perceived to be food by the majority of participants and therefore, if well accepted, they might be also shared as any other food. Sharing of supplements in foodinsecure settings has also been indicated by others (17)(18)(19) , which suggests the need to revise the approach to food assistance for PLHIV in food-insecure settings. To discourage this practice among Malawian food-insecure households, several authors have suggested considering counselling activities in health-care facilities and/or integrating HIV care in safety net programmes (7) .…”
Section: Discussionmentioning
confidence: 94%
“…These include gender, urbanization, cost of food, irregular follow up by primary care giver, poor patient-health giver relations, lack of information or not well understood information, level of education, tendency to eat out and lack of self-discipline [2,20,23]. In Kenya, non-adherence to treatment has been associated with among other things, poverty, since 46% of Kenyans live on less than a dollar per day and may not afford the recommended diet [29] taste of the food, diet monotony and sharing of food rations with other family members [11]. Studies in Kenya have shown non-adherence even when patients acknowledged that they had received dietary advice and could as well afford the recommended dietor were given food rations [3,28], implying that there could exist underlying reasons for nonadherence in such cases.…”
Section: Introductionmentioning
confidence: 99%